Back Cover: The Effect of Functional Groups in Bio‐Derived Fuel Candidates (ChemSusChem 9/2016). Issue 9 (3rd May 2016) - Jenkins, Rhodri W.; Moore, Cameron M.; Semelsberger, Troy A.; Chuck, Christopher J.; Gordon, John C.; Sutton, Andrew D.
Abstract : This Back Cover image shows the concept of linking bioderived molecules and the functional groups contained within these molecules to real transportation fuel. This article discusses the important traits that are required in a transportation fuel and looks at the effect that carbon and oxygen groups have on these properties. By making this link we hope that this will provide some insight into how to design and synthesize molecules from biomass that could yield useful transportation fuels. More details can be found in the Concept by Jenkins et al. onpage 922 in Issue 9, 2016 (DOI:10.1002/cssc.201600159 ).